Geomorphic Investigations of Newly Identified Linear Dunes in Western Wisconsin, USA - Running, Garry L.; Jansen, Erica; Coonen, Kayla (My University, 2018)
The purpose of this poster is to present results of research conducted in western Wisconsin (Buffalo, Chippewa, Southern Dunn, Eau Claire, Pepin, Pierce and St. Croix Counties). Our analysis of high resolution LiDAR-derived DEMs and soil texture data (sandy, gravel-free soil parent materials) revealed ~375 linear dunes (interpreted based on morphology), one of many sandy eolian (wind-deposited) landforms previously unknown in the study area we are investigating (sand sheets, deflation hollows, parabolic dunes, sand ramps, and eolian dammed drainages). Linear dunes were identified and mapped independently by three team members. The dunes are 40 to 2,600 m long, up to ~100 m wide, and ~1.5 to 3 m high. They also exhibit a preferred WNW to ESE orientation suggesting formation under a WNW paleowind. Preliminary age control indicates they formed from ~13 ka to 11 ka during the terminal late-Pleistocene. Their age and orientation is consistent with paleowind reconstructions based on loess distributions across the study area. Further investigations to better constrain their age, describe their internal stratigraphy (to con􀏐irm our paleowind reconstruction), and their relationship to sand stringers, similar landforms widely observed in similar landscape settings in southeastern Minnesota and elsewhere in the western Great Lakes region, are ongoing.
Color poster with text, images, maps, and graphs.
Keywords: Posters; Sand dunes; Soil chemistry